An Unusual case of neurocysticercosis leading to blindness in a young Indian male - Wadhwani, Meenakshi; Panda, Ananya; Vohra, Rajpal; Srivastava, Achal Kumar (Nepalese Journal of Ophthalmology, 2019)
Neurocysticercosis is an endemic disease in India. It is caused by infection from the larval form of Taenia solium and humans serve as the intermediate host. Its diverse manifestations include seizures, headaches, focal neurological signs. Obstructive hydrocephalus, with its potential for death is the most disastrous complication. We hereby report a case of 24 year old boy presenting with blindness without hydrocephalus.